Conference on Lasers and Electro-Optics/International Quantum Electronics Conference 2009
DOI: 10.1364/cleo.2009.cmcc2
|View full text |Cite
|
Sign up to set email alerts
|

Common-path Fourier-domain optical coherence tomography with a fiber optic probe integrated into a surgical needle

Abstract: Abstract-We have demonstrated in vivo three-dimensional imaging and estimated localized and quantitative hemoglobin oxygen saturation (SO 2 ) of blood vessel by using a simple, easy to operate common-path Fourier-domain optical coherence tomography (OCT) system. The common-path OCT system can be easily integrated with various surgical tools and we demonstrated its usefulness by imaging outer and inner intraocular tissues such as cornea and neurosensory retinal layers as well as detecting SO 2 level from a chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A probe compatible with CP-OCT has been coupled with surgical tools to investigate intra-ocular and intravitreous locations of human being and rat as well. This surgical probe also has been used in a 0.8-μm common-path Fourier-domain OCT [109][110][111][112]. The fiber bundle probe has also been demonstrated with FD-OCT to eliminate the scanning at the distal end to image the tissue during microsurgery [113,114].…”
Section: Common-path Interferometer Based Probesmentioning
confidence: 99%
“…A probe compatible with CP-OCT has been coupled with surgical tools to investigate intra-ocular and intravitreous locations of human being and rat as well. This surgical probe also has been used in a 0.8-μm common-path Fourier-domain OCT [109][110][111][112]. The fiber bundle probe has also been demonstrated with FD-OCT to eliminate the scanning at the distal end to image the tissue during microsurgery [113,114].…”
Section: Common-path Interferometer Based Probesmentioning
confidence: 99%
“…Kang et al investigated a common-path interferometer based FD-OCT [134], [136] and used this for retinal imaging applications. Other common-path interferometer based approaches for time-domain OCT, using a free space interferometer, have also been demonstrated with limited success [141], [142]. Fiber optic-based technologies have been used for both frequency-domain and time-domain common-path OCT systems [132], [133], [135]- [139], [141].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Kang et al [134] recently demonstrated the efficacy of fiber optic common-path OCT with a comparative assessment of existing endoscopic technologies. The Fourier domain common path optical coherence tomography has thus shown promising potential for intraocular surgical applications relevant to retinal surgery as the model application [134], [142], [143].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The interferometer and spectrometer design in our FD CP OCT system are described in Ref [9], shown in Fig 1.The reference surface is at the distal end of probe arm and the interference signal of reference and sample light is detected by a spectrometer. To achieve a broad bandwidth source output, multiple SLEDs were combined to serve as broadband source, which centers at 800nm.…”
Section: Common Path Octmentioning
confidence: 99%